Pengaruh Literasi Keuangan, Personality Traits, dan Pengendalian Diri terhadap Perilaku Pengelolaan Keuangan (Studi pada Penggemar Artis Thailand) - Imelda Charlyvia; Alimuddin Rizal Riva’i (Universitas Batanghari, 2023)
Financial management behavior is a person's ability to plan, budget, check, manage, control, seek and save financial funds on a daily basis. This behavior arises due to the magnitude of a person's desire to fulfill his life needs in accordance with his income level. This study aims to determine and analyze the effect of financial literacy, personal traits, and self-control on financial management behavior. The sample used was 107 respondents using a purposive sampling technique. The analytical method used in this study is multiple linear regression. The results show that financial literacy, personality traits, and self-control partially have a positive and significant effect on financial management.